The Degree of Effectiveness of the Active Learning Strategy in Improving Students' Learning in History from Teachers Perspective - Al-Freahat, Elham Hussein Ali (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the degree of effectiveness of the active learning strategy in improving students' learning in History at primary stage from teachers perspective in Ajloun Directorate. Study sample consisted of (77) male and female of History teachers. To achieve the objectives of the study, a questionnaire was used as a tool for data collection; it consisted of (23) items. The result showed that the level the degree of effectiveness of the active learning strategy in improving students' learning in History from teacher's perspective was High with (3.92) score. The finding also showed that there is no statistically significant differences between the level of History teachers sex (male and female) in addition there were statistically significant differences refers to teachers years of experience in favor of the (10 and more) years of experience. The study recommended the necessity of training students to employ the active learning strategy to develop their academic achievement.
Keywords: Effectiveness; Strategy; Active Learning; History